Prevalence of Uremic Pruritus, Its Risk Factors and Impact on Health Related Quality-Of-Life in Patients on Maintenance Hemodialysis (Academia Journal of Medicine, 2020)
Background: Renal pruritus is one of the most debilitating symptom of chronic kidney disease especially affecting patients on maintenance  hemodialysis. Subjects and Methods: It was a cross-sectional questionnaire based study. Demographic, dialysis related and biochemical  parameters of maintenance hemodialysis patients were recorded, and a pre-defined questionnaire was put to them. Severity was calculated with  12 point pruritus severity scale (PSS), health-related quality of life with SKINDEX-10, and sleep survey with ITCH-MOS. Results: The total  of 164 patients (mean age 52 ± 17years, males-57.9%, females-42.1%) completing questionnaire and laboratory analysis were included in the  study. Prevalence of pruritus was 53.7% (mild in 31.8%, moderate-45.5%, severe-22.7%). Prevalence was higher in diabetic CKD (p=0.0001),  and irregularly dialyzed patients (p=0001). The severity of pruritus correlated with older age (p=0.004), shorter dialysis vintage (p=0.000),  irregular dialysis (0.000), higher serum phosphorus (0.003), and parathyroid hormone level (0.000) and higher calcium-phosphorus product  (0.001). SKINDEX-10 showed worsening symptoms, emotional and functional quality of life (p=0.000), and poorer sleep quality and quantity  as per ITCH-MOS (0.000), with increasing severity of itching. Conclusion: Renal itch is highly prevalent in maintenance hemodialysis  patients, most severely affecting diabetics, elderly, irregularly dialyzed patients, with poorly controlled mineral bone parameters. The severity  correlates with worsening sleep and overall quality-of-life.
Keywords: Uremia; uremic/renal pruritus; maintenance hemodialysis; health-related quality of life; sleep